Transients of modern power electronics - Bai, Hua, 1980-; Mi, Chris (Chichester, U.K. : John Wiley & Sons, 2011)
'This book will investigate the short-timescale transient phenomena (from microsecond to nanosecond) of power electronic systems, with a focus on high-power converters for hybrid electric vehicles and renewable energy systems. The authors will provide guidelines for design that improve system reliability, a crucial issue for high power and high voltage power electronic systems. The book will explore the interrelations among various subsystems with different scales of time constants, and thereby set up a theoretical framework and relevant methodology for the design, modeling and prototyping of modern power electronics converters. Topics to be covered include an introduction to the fundamentals of transients in power electronics; modeling methods for power electronic subsystems; switching processes of semiconductors; dead-band effect and minimum pulse width; modulated error; abnormal pulses and sneak pulse, and concluding with a look to future trends within this field'--
Includes bibliographical references and index.
Keywords: Power electronics; Transients (Electricity); Electric current converters -- Design and construction